Limited Progress in Increasing Coverage of Neonatal and Child-health Interventions in Africa and Asia (Journal of Health, Population and Nutrition, 2010)
The study was conducted to analyze recent trends in the coverage of selected child-survival interventions. A systematic analysis of the coverage of six key child-health interventions in 29 African and Asian countries that had two recent demographic and health surveys-the latest one carried out in 2001 onwards and the immediately preceding survey conducted after 1990-was undertaken. A regression model was used for examining the relationship between the changes in the coverage of interventions and the changes in rates of mortality among children aged less than five years (under-five mortality). A limited increase in the coverage of key child-health interventions occurred in the past 5-10 years in these 29 countries in sub-Saharan Africa and Asia. More than half of the countries had no significant improvement or a significant reduction in the coverage of oral rehydration therapy (ORT) for diarrhoea (17/29) and care-seeking for acute respiratory infection (ARI) (16/29). Results of multivariate analysis revealed that increases in the coverage of early initiation of breastfeeding, ORT for diarrhoea, and care-seeking for ARI were significantly associated with reductions in under-five mortality. The results of this analysis should serve as a wake-up call for policymakers and programme managers in countries, donors, and international agencies to accelerate efforts to increase the coverage of key child-survival interventions. The following three main actions are proposed: setting of the clear target; mobilization of resources for increasing skilled birth attendants and health workers trained in integrated management of childhood illness; and implementation of community-based approaches. Key words: Child health; Child survival; Infant health; Infant survival; Interventions; Asia; Africa DOI: 10.3329/jhpn.v27i6.4327 J Health Popul Nutr 2009 Dec; 27(6): 755-762